A Note on Some Properties of the Weighted 𝑞-Genocchi Numbers and Polynomials - L. C. Jang (Journal of Applied Mathematics)
We consider the weighted 𝑞-Genocchi numbers and polynomials. From the construction of the weighted 𝑞-Genocchi numbers and polynomials, we investigate many interesting identities and relations satisfied by these new numbers and polynomials.